Determination of radon gas concentrations 222Rn in water samples of Rivers and ground wells in Basrah Governorate, Iraq - Ali, Master A. (Mesopotamian Journal of Marine Sciences, 2021)
In this study, 52 samples were collected from natural water taken from selected areas from (Rivers, groundwater wells) in Basrah Governorate-Southern Iraq for the period from February - April 2020, to determine the concentrations of the radon gas (222Rn) emitted from the selected and newborn samples of the radioactive element Radium 226Ra located in the series of uranium 238U and calculate the annual effective dose. Solid state Nuclear Track Detectors SSNTDs have been used, a long-term passive measurement method for the emission of (α particles) with the CR-39 detectors, LR-115typeII and a method for measuring the activity with a fast electronic device called RAD7. The results of the study showed that the lowest concentration of radon gas in samples of River water was 196 ±12 Bq.m-3 was in the sample No. W13 water of Garma River, and that the largest concentration was 16217 ±97 Bq.m-3 sample No. W9 from Al Khoura River. As for the radon gas concentration in groundwater wells, its highest concentration reached 22415 ±143 Bq.m-3 in sample No. W36 from Aldawajin well-2, and the lowest concentration was 682 ±46 Bq.m-3 in sample No. W24 in a well at Al-Barjisiah and the general average of radon gas concentration in all the study samples was 7320 Bq.m-3, the annual effective dose of water was estimated and it was found that the highest value was 1.136 mSv.y-1 in sample No. W36 and this value falls outside the internationally approved limit By the World Health Organization WHO, 0.1 mSv.y-1 In general. It was found that radon concentrations in water samples of Rivers and groundwater wells selected from Basrah Governorate-Southern Iraq falls within the limits of the permissible value of 11000 Bq.m-3 for surface water and 20000Bq.m-3 for groundwater wells, according to the US Environmental Protection Agency EPA, with the exception of some samples of Rivers and underground wells, which have recorded values higher than that value, and they may pose a risk on the health of farmers in those areas.